Excitation of wake field and transition radiation in a semi-infinite waveguide by a relativistic electron bunch - Balakirev, V.A.; Onishchenko, N.I.; Sidorenko, D.Yu.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2002)
The theoretical investigations and simulation are performed for the emission of a relativistic electron bunch
during the injection into a semi-infinite vacuum/dielectric waveguide. The power and the frequency spectrum of
high intensity pulse of ultra-wideband transition radiation, excited by a finite size electron bunch in a vacuum
waveguide, are calculated numerically. It is shown that in a dielectric waveguide the short pulse of Cherenkov wake
field drifts behind the relativistic bunch with the group velocity.